Deeper Chandra follow-up of cygnus TeV source perpetuates mystery - Butt, Yousaf M. (2006)
A 50 ks Chandra observation of the unidentified TeV source in Cygnus reported by the HEGRA collaboration reveals no obvious diffuse X-ray counterpart. However, 240 pointlike X-ray sources are detected within or nearby the extended TeV J2032+4130 source region, of which at least 36 are massive stars and two may be radio emitters. That the HEGRA source is a composite, having as a counterpart the multiple pointlike X-ray sources we observe, cannot be ruled out. Indeed, the distribution of pointlike X-ray sources appears nonuniform and concentrated broadly within the extent of the TeV source region. We offer a hypothesis for the origin of the very high energy gamma-ray emission in Cyg OB2 based on the local acceleration of TeV-range cosmic rays and the differential distribution of OB versus less massive stars in this association.